Concerns of adult siblings of persons with autism - Sorongon, Rosalyn Marie Gizon (2008)
This qualitative study attempted to explore the concerns of adult siblings of persons with autism (CWA) given their personal characteristics particularly gender, age and birth order. An open-ended researcher-designed instrument was administered to 30 adult siblings with ages 20-39 years old, single and married, and currently in college or had college degrees. This was followed by interviews. The adult siblings' concerns revolved around the following: physical care of the SWA, functioning level of the SWA, people's attitude towards the SWA, survival in the community, family relationships, own self, parental expectations, knowledge on autism, sexuality, financial and continuing involvement in the life of SWA. Adult siblings who are first-born are consistent in their desire to initiate involvement regarding matters related to the current and future responsibilities of caring for the SWA.
Computer printout.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Autism -- Philippines; People with mental disabilities -- Home care -- Philippines; People with mental disabilities -- Family relationships -- Philippines; Parent and adult child -- Philippines